Clinical efficiency and dermoprotection of 2-ethyl-6-methyl-3-hydroxypyridine succinate drug in case of psoriasis: from the antioxidation point of view - Visir, V. A.; Makurina, G. I.; Візір, Вадим Анатолійович; Макуріна, Галина Іванівна (Zaporizhzhia state medical university, 2016)
Objective. To study the clinical significance of oxidative processes modulation within frames of 2-ethyl-6-methyl-3-hydroxypyridine succinate dermatropic efficiency assessment in patients with psoriasis affected by arterial hypertension. Materials and methods. The results of this study are based on data of comprehensive examination and supervision of 30 patients suffering from psoriasis with different clinical forms such as normal levels of blood pressure (the control group) or in combination with hypertension (the study group). Results. The comparative description of the antioxidative therapy efficiency was performed by the end of treatment. The findings showed significantly positive antioxidant-dependent mechanisms of 2-ethyl-6-methyl-3-hydroxypyridine succinate clinical efficiency in patients with psoriasis affected by arterial hypertension. In case of patients with combined psoriasis and essential hypertension course 2-ethyl-6-methyl-3-hydroxypyridine succinate therapy caused reliable decrease of free-radical oxidation intensification in particular nitrosative (reliable decrease of nitrotyrosine) and oxidative (negative dynamics of endothelin-1 and positive dynamics as to glutathione metabolism) stresses. That, in its turn, decreased the evidence of apoptotic and inflammatory processes (caspase-8 and TNF-α regress) both directly and indirectly by means of mediating anti-inflammatory effect on endothelium cells and macrophages of anticoagulant proteinase through endothelial protein C receptor (EPCR) with production of components and structures of extracellular matrix and disturbance of microcirculation. Thus, it determines the key pathogenetic aspects of psoriasis. The decrease of VEGF expression indicators level (vascular endothelial growth factor) and serotonin, associated with this combined therapy, had stipulated statistically significant positive clinical and subjective effect in form of regress of dermatological changes (PASI index), decrease of itch (optimization of serotonin biosynthesis and reduction of methionine conversion (with homocysteine formation)) and improvement of life quality. Conclusions. Taking into account potential influence of 2-ethyl-6-methyl-3-hydroxypyridine succinate on these pathophysiological predictors and pathogenesis, which are to some extent involved in formation and progression of psoriatic disease, use of 2-ethyl-6-methyl-3-hydroxypyridine succinate is sufficiently effective in conditions of psoriasis therapy optimization. Рекомендації щодо терапії пацієнтів, які страждають одночасно на псоріаз та артеріальну гіпертензію, вкрай нечисленні. Мета роботи – вивчити клінічну значущість модуляції оксидативних процесів у рамках оцінювання дерматотропної ефективності 2-етил-6-метил-3-гідроксипіридину сукцинату у хворих на псоріаз на тлі артеріальної гіпертензії. Матеріали та методи. Результати цього дослідження засновані на даних комплексного обстеження та спостереження за 30 пацієнтами, які страждають на різні клінічні форми псоріазу як з нормальними цифрами артеріального тиску (контрольна група), так і в поєднанні з артеріальною гіпертензією у вигляді гіпертонічної хвороби (основна група). Результати. Здійснили порівняльну характеристику антиоксидантної ефективності терапії наприкінці лікування. Дані показали доволі позитивні антиоксидант-залежні механізми клінічної ефективності 2-етил-6-метил-3-гідроксипіридину сукцинату у хворих на псоріаз на тлі артеріальної гіпертензії. У хворих із поєднаним перебігом псоріазу та гіпертонічної хвороби терапія 2-етил-6-метил-3-гідроксипіридину сукцинатом сприяла вірогідному зниженню проявів інтенсифікації вільно-радикального окислення, зокрема нітрозуючого (вірогідне зменшення нітротирозину) та оксидативного (негативна динаміка ендотеліну-1 і позитивна щодо метаболізму глутатіону) стресів, що, своєю чергою, зменшувало вираженість апоптотичних і запальних процесів (регрес каспаз-8 і ФНП-альфа) як безпосередньо, так і опосередковано через дію антикоагулянтної протеїнази на клітини ендотелію та макрофаги через ендотеліальний рецептор протеїну С (EPCR), регулюючи продукцію компонентів і структур екстрацелюлярного матриксу з порушенням мікроциркуляції, детермінуючи таким чином ключові патогенетичні аспекти розвитку псоріазу. Зниження рівня показників експресії VEGF (регулятор утворення мікросудин) і серотоніну на тлі цієї комбінованої терапії зумовлювало статистично значущий позитивний клінічний і суб’єктивний ефект у вигляді регресу дерматологічних змін (індекс PASI), зменшення свербежу (оптимізація біосинтезу серотоніну та редукція конвертації метіоніну з утворенням гомоцистеїну), поліпшення якості життя. Висновки. З урахуванням потенційного впливу 2-етил-6-метил-3-гідроксипіридину сукцинату на відзначені патофізіологічні предиктори та ланки патогенезу, які в однаковій мірі залучаються при формуванні та прогресуванні псоріазу, можна зробити висновок: застосування цього препарату є доволі перспективним у плані оптимізації терапії досліджуваного дерматозу.
Клінічна ефективність і дермопротекція 2-етил-6-метил-3-гідроксипіридину сукцинату при псоріазі: погляд із позицій антиоксидації
Keywords: antioxidants; pasi index; life quality; 2-ethyl-6-methyl-3-hydroxypyridine Succinate; clinical study; антиоксиданти; індекс PASI; якість життя; 2-етил-6-метил-3-гідроксипіридину сукцинат; клінічне дослідження